The Effect of Adding Adsorbents on Main Indicators of Produced Water Purification - Havidh Pramadika; Arinda Ristawati; Bayu Satiyawira; Aqlyna Fattahanisa; Ghanima Yasmaniar; Muhammad Ridhal Malik Syafrudin (Penerbitan Universitas Trisakti, 2023)
Formation water is a by-product of oil and gas processing. This formation water is very different from fresh water because formation water contains harmful chemicals and other elements contained in oil or gas. To prevent formation water from contaminating the environment, it is necessary to reduce the formation water content using an adsorbent. Some of the parameters that indicate reduced mineral and chemical content that must be considered for this research are pH, TDS (total dissolved solid), SG (specific gravity), and salinity values. In this study observed changes in these parameters with the administration of adsorbents. Two types of adsorbents used are bagasse and bentonite. The parameters of pH and TDS were measured using litmus paper and TDS paper respectively. While SG and salinity were measured using a salinity hydrometer. The process of giving the adsorbent causes a decrease in these four parameters. The addition of 3 grams of bagasse caused the pH, TDS, SG, and salinity of the formation water to decrease to 7.8, 3086 ppm, 1008 and 12 ppt, respectively. While the addition of 3 grams of bentonite caused these four parameters to decrease to 7.8, 2720 ppm, 1010 and 14 ppt respectively.